Kajian Ketelitian Current Transformer (CT) Terhadap Kesalahan Rasio Arus pada Pelanggan 197 kVA - Aas Wasri Hasanah; Tony Koerniawan; Yuliansyah Yuliansyah (Sekolah Tinggi Teknik PLN, 2019)
With the growth of electricity consumption getting bigger, the possibility of greater losses arises from measuring energy in customers. One cause of the losses due to mistakes in flow ratio CT (Current Transformer) installed on APP Box indirect measurement. Necessary to test the CT accuracy class to determine the current ratio error limits set by the standard PLN. Then do the replacement on the CT accuracy class to resolve this issue. This activity is done at the customer PT. Astra Int Auto 2000 by replacing the CT accuracy class of 0.5 becomes 0,5S. There is a comparison of the measurement between the two different classes. Based on the results of tests performed, a decline in the current ratio error before and after the replacement of accuracy class. After calculating the error margin of the second flow ratio CT installed that are not measured by the energy meter. This Value kWh that is the losses to PT. PLN (Persero) Area Depok. So understanding CT as one of the tools of measurement (instrumentation) should be changed to a point of transaction (point of transaction). So that the revenue gains kWh a business orientation that is fundamental to PLN by pressing slightly possible energy losses (losses) that occur in the measurement system.